Improvement of The Structure of Training Tools in the Professional Education System of the Republic of Uzbekistan Based on the Principles of Their Composition - Khaidarov, B. M. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article reveals the relevance of improving the structure of textbooks in the vocational education system in connection with the reform of vocational education, which is currently being carried out in the Republic of Uzbekistan. As a condition for improving the structure of teaching aids for the system of professional training of specialists in the Republic of Uzbekistan, it is proposed to implement the question-answer principle when compiling them. The article provides various definitions of tutorials. The essence of the proposed structure is revealed. The conclusion is made about the need to revise the content and structure in accordance with the principles of compiling textbooks with a competence-based approach.